MEASUREMENT OF DEFORMATION IN ALUMINA SAMPLES INDENTED AT HIGH STRAIN RATES - Dancer, C; Curtis, H; Bennett, S; Petrinic, N; Todd, R (2011)
In this paper we describe the use of Cr3+ fluorescence mapping for the study of residual stress and plastic deformation induced in alumina targets by dynamic impact with sharpened tungsten carbide projectiles. A range of alumina samples in the form of small discs with varying glass content, purity and grain size were impacted by small projectiles accelerated to around 100 m/s using a gas gun. Post-test characterisation of the targets was carried out using 3D optical microscopy, scanning electron microscopy, and by Cr 3+ fluorescence mapping of the residual stress and plastic deformation in the impacted region. The response of the alumina was found to vary according to its glass content and grain size, and the materials were ranked according to their response under impact.